Novel Micrococcus unila to Produce Glucosamine by Solid-state Fermentation of Shrimp Shell Waste - Setiawan, Wawan Abdullah; Setiawan, Andi; Salsabila, Nafila Khansa; Widyastuti, Widyastuti; Laila, Aspita; Juliasih, Ni Luh Gede Ratna; Irawan, Bambang; Ahmadi, Peni; Apriliana, Ety; Arai, Masayoshi; Hendri, John (Science and Technology Indonesia, 2024)
This study aimed to assess glucosamine production through enzymatic activity, utilizing actinomycetes sourced from shrimp shell waste (SSW) in a solid-state fermentation (SSF) process. A total of 16 actinomycetes underwent chitinase activity screening, and the strain exhibiting the highest chitinolytic index was chosen for subsequent morphological and phylogenetic analyses. High Performance Liquid Chromatography (HPLC) was employed to analyze glucosamine produced from the bioconversion of SSW via SSF. Optimal conditions for glucosamine production were determined by varying time, pH, and temperature. Isolate 18D36-A2 showed the highest chitinolytic index of 1.02 in the 32-mm clean zone. Phylogenetic analysis revealed 97% similarity to the genus Micrococcus, identifying it as a novel Micrococcus unila strain 18D36-A2 and deposited in GenBank. This isolate effectively converted shrimp shells. The findings showcase the bioconversion of SSW to glucosamine through SSF using the Micrococcus unila 18D36-A2. Furthermore, this study establishes a foundation for future research on environmentally friendly and sustainable designs for glucosamine production.